Advertising as Information: Matching Products to Buyers - Kyle Bagwell; Garey Ramey (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1992)
We consider communication of quality via cheap talk and dissipative advertising, when consumers have heterogeneous tastes for quality. For search goods, cheap talk communicates quality when fixed costs are roughly constant across quality levels, while if fixed costs vary greatly with quality, then firms having the higher-fixed-cost quality level use dissipative advertising. Further, product differentiation (generically) cannot occur in the absence of advertising. For experience goods, quality can be communicated by cheap talk in a range where low-quality firms have greater fixed costs, and low-quality firms use dissipative advertising if their fixed costs are greater still.
Keywords: 330